2021
DOI: 10.3390/cancers13215423
|View full text |Cite
|
Sign up to set email alerts
|

Can Conization Specimens Predict Sentinel Lymph Node Status in Early-Stage Cervical Cancer? A SENTICOL Group Study

Abstract: Background: The prognosis of patients with cervical cancer is significantly worsened in case of lymph node involvement. The goal of this study was to determine whether pathologic features in conization specimens can predict the sentinel lymph node (SLN) status in early-stage cervical cancer. Methods: An ancillary analysis of two prospective multicentric database on SLN biopsy for cervical cancer (SENTICOL I and II) was carried out. Patients with IA to IB2 2018 FIGO stage, who underwent preoperative conization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(107 reference statements)
1
5
0
Order By: Relevance
“…(2.8%) in a prospective study [20]. Likewise, in the prospective SENTICOL study, the authors found a low risk of metastases in tumours with < 10 mm depth of invasion and no LVSI (3% isolated tumour cells and 1% micrometastases) [21]. In contrast, we found a tumour size of ≤20 mm with LVSI and a depth of invasion > 10 mm to be related to a risk of 18.3%.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…(2.8%) in a prospective study [20]. Likewise, in the prospective SENTICOL study, the authors found a low risk of metastases in tumours with < 10 mm depth of invasion and no LVSI (3% isolated tumour cells and 1% micrometastases) [21]. In contrast, we found a tumour size of ≤20 mm with LVSI and a depth of invasion > 10 mm to be related to a risk of 18.3%.…”
Section: Discussionsupporting
confidence: 61%
“…Preoperative estimation of the depth of invasion may be challenging if the tumour is only partially sampled-for example, after non-radical conization. However, Balaya et al [21] showed that final depth of invasion (≤10 mm or > 10 mm) is predicted correctly from conization specimens in 92% of the cases, irrespective of margin status. Moreover, interobserver agreement has been reported to be high (83%) in quantitative assessment [33].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Balaya and colleagues analyzed the risk factors that used to be associated with a higher incidence of positive lymph nodes in conization specimens: a depth stromal invasion <10 mm and no LVSI had a lower risk of micro- and macro-metastasis in SNL [ 5 ].…”
mentioning
confidence: 99%